Placenta, Secret Witness of Infant Morbidities: The Relationship Between Placental Histology and Outcome of the Premature Infant - Ufuk ÇAKIR; Duran YILDIZ; Dilek KAHVECIOĞLU; Emel OKULU; Serdar ALAN; Ömer ERDEVE; Aylin OKÇU HEPER; Begüm ATASAY; Saadet ARSAN (Federation of Turkish Pathology Societies, 2019)
Objective: The microscopic and macroscopic features of the placenta can contribute to the clinical understanding of premature delivery. The aim of our study was to figure out the relationship between the histopathological findings of the placentas of premature deliveries and its effects on neonatal morbidity and mortality. Material and Method: The placentas of 284 singleton preterm infants with <35 weeks of gestation were examined. three groups created as the normal, chorioamnionitis and vasculopathy according to histopathological findings in placentas subjects. Results: The mean gestational age of the infants in the study group was 30.5 ± 3.2 weeks, and the mean birth weight was 1588 ± 581 g. The pathology was normal in ninety-six (33.8%), vasculopathy in 153 (53.9%) and chorioamnionitis in 35 (12.3%). The gestation age of the infants was lower in the chorioamnionitis group. Moreover, retinopathy of prematurity, early onset neonatal sepsis, and duration of respiratory support were found to be higher in the chorioamnionitis group. In the vasculopathy group, preeclampsia and small for gestational age were found to be significantly higher. Conclusion: Histopathological findings of the placentas from preterm deliveries provided important data in determining the etiology of preterm delivery and outcomes of infants. Infants delivered by mothers with chorioamnionitis were particularly found to be more preterm, and these preterm infants would have a longer hospital stay, higher respiratory support requirement, and more serious morbidities.